Effectiveness of the management of major depressive episodes/disorder in adults with comorbid chronic physical diseases: a protocol for a systematic review and meta-analysis. Issue 7 (20th July 2017) - Martínez, Pablo; Castro, Ariel; Alonso, Diego; Vöhringer, Paul A; Rojas, Graciela
Abstract : Introduction: Depression is a global-scale public health problem, and a significant association has been established between depression and chronic physical diseases. This growing comorbidity poses a challenge to healthcare systems. We aim to assess the effectiveness of the management of major depressive episodes/disorder in adults with comorbid chronic physical diseases. Methods and analysis: We will conduct a systematic review and meta-analysis of randomised clinical trials. Two databases MEDLINE and Cochrane Library (Cochrane Database for Systematic Reviews and CENTRAL), as well as the reference lists of the included articles, will be searched for studies either in English or Spanish with published results within the 2005–2015 period. Studies must fulfil the following conditions: (1) participants aged 18 years or older, diagnosed as having a major depressive episodes/disorder according to standardised criteria and chronic physical diseases; (2)interventions (be it pharmacological, psychological, psychosocial or a combination) must be compared with control conditions (other 'active' intervention, treatment as usual, waiting list or placebo); (3)and must report reduction in depressive symptoms after treatment, response to treatment, remission of major depressive episodes/disorder and significant improvement in quality of life. Data extraction, risk of bias evaluation, results summarisation and quality of the evidence (GRADE) will be performed as recommended by the Cochrane Collaboration. A qualitative synthesis and a random effects meta-analysis will be carried out. Effect sizes will be calculated (relative risk and Cohen's d), I 2 and Q statistics will be employed to study heterogeneity and publication bias analysis will be performed. Subgroup analyses and meta-regression will be carried out. Ethics and dissemination: Results are expected to be published in specialised peer-reviewed journals (preferred topics: Mental Health, Psychology, Psychiatry and/or Systematic Reviews) and dissemination activities will be targeted to all the healthcare providers. Trial registration number: International Prospective Register of Systematic Reviews (CRD42016029166) submitted on 11 January 2016.